Pengaruh Citra Merek, Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan: (Studi Pada Pengguna Jasa PT Serasi Manunggal Sejahtera Cikokol, Tangerang Banten) - Arif Prasetiyo; Ravindra Safitra Hidayat; Maruji Pakpahan; Feby Lukito Wibowo (LPPM Politeknik Pratama, 2025)
This study examines the effect of brand image, promotion, and service quality on customer satisfaction at PT Serasi Manunggal Sejahtera. The research employed a quantitative method with purposive sampling, involving 100 respondents determined using the Lemeshow formula. Data were collected through a Likert-scale questionnaire and analyzed using Microsoft Excel 2019 and SPSS 25. The analysis included validity, reliability, normality, and heteroscedasticity tests, along with t-tests, determinant tests, and multiple regression analysis. The results show that brand image (X1), promotion (X2), and service quality (X3) each have a significant positive effect on customer satisfaction.